Reflections on health care consumerism: insights from feminism - Williamson, Charlotte (Health Expect, 2001)
Health care consumerism is a movement concerned with patients’ interests in health care, crucially those that are repressed or partly repressed by dominant interest‐holders. Like feminism, health care consumerism attracts dislike and confusion as well as enthusiasm. But just as the voicing of women’s repressed interests leads to their gradual acceptance by dominant interest‐holders, so does the voicing of patients’ repressed interests.